A lightning attachment model to UHV transmission lines based on FEM - Ma, Ziwei; Jasni, Jasronita; Ab Kadir, Mohd Zainal Abidin; Azis, Norhafiz (IEEE, 2023)
Developing a numerical simulation model for shielding failure evaluation of UHV transmission lines is an urgent task. In this article, a dynamic leader propagation model of lightning attachment to UHV transmission lines was developed based on FEM. The lightning downward leader descending vertically at a speed of 2×105m/s from a distance of 50 m from the side of the UHV transmission line was considered as a lossy conductor. Peek’s formula was used for initial corona inception criterion. The streamer space charge and the leader length were calculated by using the voltage distortion method. The upward leader was assumed to propagate in the direction of the maximum field strength. The final jump was considered to occur once the average electric field strength of the remaining gap reaches 450 kV/m. Without considering the operating voltage, the simulation result shows that the striking distance of the ground wire under the return stroke current of 10 kA, 20 kA, 30 kA, 40 kA and 50 kA is 54 m, 94 m, 143 m, 157 m, and 234m respectively. A new expression of rs=7.2I0.87p for the striking distance calculation based on LPM was proposed. The striking distance calculated by this new model is between the EGM empirical model and theoretical model, which proves that the model is reasonable.